2022
DOI: 10.54558/jiss.1137116
|View full text |Cite
|
Sign up to set email alerts
|

Sukuk ve Ekonomik Büyüme İlişkisi: Türkiye Üzerine Bir Uygulama

Abstract: Purpose: The aim of this paper is to investigate the relationship between sukuk issued by participation banks and economic growth in Turkey. Method: In this paper, Engle-Granger co-integration and Grenger causality approaches were used as methods. The sukuk issued by all participation banks operating in Turkey and real GDP figures have been analyzed for the period of 2013Q4-2021Q3. Findings: As a result of the Engle-Granger co-integration test, long-term statistically significant co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…We can interpret this result as that economic growth is a factor that enables participation banks to increase the issuance of sukuk. This result we obtained is similar to the results obtained by Avcı (2020) and Dilber (2022). On the other hand, while there is a one-way causality relationship from INF variable to GDP, there is a bidirectional causality relationship between GDP and GCF variable.…”
Section: Empirical Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…We can interpret this result as that economic growth is a factor that enables participation banks to increase the issuance of sukuk. This result we obtained is similar to the results obtained by Avcı (2020) and Dilber (2022). On the other hand, while there is a one-way causality relationship from INF variable to GDP, there is a bidirectional causality relationship between GDP and GCF variable.…”
Section: Empirical Findingssupporting
confidence: 91%
“…On the other hand, in the research conducted by Alkhwaja (2019), which is one of the rare studies conducted specifically for Türkiye on this subject in the literature, it's claimed that sukuk issuances have an increasing effect on economic growth (supporting our result), but no econometric analysis was used in the study. The results obtained from the research conducted by Dilber (2022), which is another one of the rare studies conducted specifically in Türkiye, support the results we obtained in our study. Finally, according to the result of the study conducted by Orhan & Tırman (2021), it was suggested that sukuk issued by participation banks play a role in reducing economic growth.…”
Section: Conclusion and Recommendationssupporting
confidence: 91%
See 1 more Smart Citation
“…Literatürle karşılaştırıldığında kamu sağlık ve kamu eğitim harcamalarının sosyal refah üzerinde etkili olduğunu tespit eden Gupta, vd. (1998), Davies (2009), Haile ve Zarazua (2018), Erdem ve Çelik (2019); kamu sağlık harcamalarının sosyal refah üzerinde etkili olduğunu tespit eden Razmi (2012), Çelikkaya ve Sezgin (2015), Mirahsani (2016), Yalçın ve Çakmak (2016), Çalışkan ve Eğmir (2020), Geyik ve Aydın (2021), Akbar, vd. (2021) çalışmaları ile araştırma sonuçları paralel çıkmıştır.…”
Section: Sonuç Ve Değerlendi̇rmeunclassified